Freedom of Information Acts in the Developing World: Lessons from the Caribbean for the Bahamian Experience - Benjamin, Lisa (International Journal of Bahamian Studies, 2017)
Freedom of Information Acts (FOIAs) can provide countries with a platform to enshrine transparency, deepen democracy and combat corruption. A number of FOIAs or Right to Information Acts have been passed in the last 20 years, particularly in developing countries and including in the Caribbean region. These initiatives have encountered similar problems, including lack of implementation and enforcement, potentially due to weak institutional systems. The lack of implementation may also be due to contradictory domestic incentives; FOIAs are designed to induce transparency and the provision of information, but also impose constraints and administrative burdens on governments. This article looks at the international context of FOIAs and analyses some of the recent problems of implementation, particularly in developing countries and specifically in the Caribbean region. The article then takes a detailed look at the amendment process and passage of the FOIA 2017 Act in The Bahamas, which is illustrative of these conflicting incentives.